The synergies of the Italian wine and tourism sectors - Fabio Gaetano Santeramo; Antonio Seccia; Gianluca Nardone (Wine Economics and Policy, 2017)
Italy is a worldwide known destination for tourism. In the Italian food industry, wine is a major sector. We analyse the synergic relations between the domestic tourism in Italy and wine industry exploring data on flows of domestic tourism among the Italian regions and key indicators for the wine industry. The region of origin of tourists is a determining factor in the choice of destination; we also highlight the role of customer loyalty. The political implications are relevant: institutions and political actors could exploit the synergies between the tourism and the wine industries by promoting excellence in wine.